Effect of Sea Cucumber on Reducing Periwound Maceration and Inflammation-Related Indicators in Patients with Diabetic Foot Ulcers Indonesia - Haryanto Haryanto; Defa Arisandi; Makoto Oe; Kazuhiro Ogai; Suriadi Suriadi; Mayumi Okuwa; Junko Sugama (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: Maceration is one of the problems affecting the healing process of diabetic foot ulcers (DFUs). In complementary therapies, sea cucumber is known to have higher absorbency. However, there are few studies on the reducing of periwound maceration and inflammation-related indicators in DFU.Methods: This was an observational study at a wound care clinic in Indonesia. Thirty-one DFU patients received treatment with sea cucumber were enrolled in the study. As control samples, 35 DFU patients treated with honey were also included. All were new occurrence DFU and had maceration at the baseline. The maceration area and inflammation-relate indicators including TNF-, MMP-2, and MMP were measured on baseline and week 4.Results: There were no significant differences between two groups at the baseline. In the multiple linear regression model, sea cucumber significantly associated with the proportion of maceration reduction than honey at week 4 (β＝0.520, p=0.001). There were no significant differences between two groups in levels on TNF-α, MMP-2, and MMP at week 4.Conclusions: Our results demonstrated that sea cucumber might be appropriate for reducing DFU periwound maceration.